Observations on the Electrical Properties of Al-Sic Composite - Al-Nasrawy, Dunia K M; Al-Sarraj, Ziyad S Ahmed; Issa, Tarik T; Jassim, Samer G H (Al-Nahrain Journal of Science, 2012)
The influence of SiC particulates addition on the electrical behaviors of Al / SiC matrix composites was studied. The composited samples were prepared from Al-SiC powdered mixtures having different SiC content in the range of 40-70 wt% SiC particulates with particle sizes lower than 45- μm. The resultant powders were then uniaxially pressed in cylindrical steel die to obtain a compact disc-shaped of 1.5 cm in diameter. The compacts were sintered in the temperature range of 800 ˚C and 1100 ˚C. Electrical and dielectric properties (a.c. Conductivity, dielectric constant, dielectric loss, and dielectric loss factor) were measured for these sintered samples in the frequency range 200 Hz – 6GHz. From the results obtained it was concluded that the formation of new phases (as proved by XRD) plays a major role in the properties of these composites. Also a jump-like behavior in the measured electrical conductivity and the abrupt changes in the dielectric constant behaviors suggest frequency- dependent two- mechanisms for conduction at different SiC content.